The Effect of Weight Training and Reaction Speed ​​on Gyaku Tsuki Punches in INKANAS Selayar Karate Sports - Adil, Ahmad; Bachtiar, Ishak; Fahrizal; Kamaruddin, Ilham (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to look at the effect of weight training and the hand reaction speed of the Gyaku Tsuki Punch on Inkanas Selayar Karate Sports. This type of study is a 2x2 factorial experiment. The research population included all Karate sports from Inkanas Selayar, with a total of 70 research samples. The sampling technique utilized the entire population, and the group division was based on matching ordinal pairs. The data analysis techniques used in this study were the 2x2 factorial analysis technique and the Tukey test with SPSS version 20.00 at the significant level of 95%, or α 0.05. The analysis revealed that: (1) Increasing the number of push-ups has a significant impact on gyaku tsuki stroke in Karate Sports of lnkanas Selayar, as evidenced by an increase in the mean from 19.8000 to 35.2500, with an observation of -16.359 > ttable 2.093 and the significant value 0.000 < ± 0.05; (2) There is an influence of pull-up training on gyaku tsuki stroke in Karate Sports oflnkanas Selayar, as proven by the increasing of the mean from 19.6500 to 39.1000 with tobservation -22.093 > ttable 2.093 and the significant value 0.000 < α 0.05. (3) Fcount 94.111 indicates a significant difference between push-up and pull-up training on the gyaku tsuki stroke in Karate Sports of Inkanas Selayar. The ttable value is 2.093, indicating a significant difference between push-up and pull-up training on the gyaku tsuki stroke in Karate Sports of Inkanas Selayar. ttable = 4.113 or significant value 0.000 < α 0.05, (5) there are differences of influence of gyaku tsuki stroke between high reaction speed groups by using push-up training and pull-up training with significant value 0.000 < α 0.05, and the high reaction speed trained by using pull-up is better than using push-up exercise, and (6) there are differences of gyaku tsuki stroke between low reaction speed groups by using push-up workout and pull-up training with significant value 0.000 < α 0.05, and the low reaction speed trained by using push-up is better than using pull-up exercice.